1998
DOI: 10.1002/j.1552-4604.1998.tb04398.x
|View full text |Cite
|
Sign up to set email alerts
|

Protease Inhibitors as Inhibitors of Human Cytochromes P450: High Risk Associated with Ritonavir

Abstract: Four protease inhibitor antiviral agents (ritonavir, indinavir, nelfinavir, saquinavir) were evaluated as in vitro inhibitors of the activity of six human cytochromes using an in vitro model based on human liver microsomes. Ritonavir was a highly potent inhibitor of P450-3A activity (triazolam hydroxylation), having inhibitory potency slightly less than ketoconazole. Indinavir was also a potent 3A inhibitor, while nelfinavir and saquinavir were less potent. Ritonavir had high inhibition potency against cytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
143
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 235 publications
(147 citation statements)
references
References 24 publications
3
143
0
1
Order By: Relevance
“…All currently available PIs are inhibitors of CYP3A with inhibitory activities ranging from weak (saquinavir) to potent (ritonavir) [4][5][6][7]. Both indinavir and ritonavir also inhibit CYP2C and −2D6 but to a much lesser extent than CYP3A [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All currently available PIs are inhibitors of CYP3A with inhibitory activities ranging from weak (saquinavir) to potent (ritonavir) [4][5][6][7]. Both indinavir and ritonavir also inhibit CYP2C and −2D6 but to a much lesser extent than CYP3A [7].…”
Section: Discussionmentioning
confidence: 99%
“…Efavirenz is converted to inactive metabolites by the cytochrome P450 enzymes, primarily CYP3A4 and CYP2B6 [2,3]. Since all currently available PIs are CYP3A4 inhibitors with varying inhibitory and induction activities, significant drug interactions have been reported when efavirenz and PIs are used in combination [4][5][6][7]. It has been reported that ritonavir produced a 21% increase in efavirenz exposure, whereas the hepatic clearance of efavirenz was unaltered by weaker inhibitors, such as indinavir, nelfinavir or saquinavir [8].…”
Section: Introductionmentioning
confidence: 99%
“…A tryptamine concentration of 100 µM was chosen because at that concentrations, no or only slight inhibition could be considered as clinically irrelevant. Clinically relevant inhibitors showed IC50 values of about 100 µM (Bertelsen et al, 2003;Brosen et al, 1993;Burt et al, 2010;Ewald and Maurer, 2008;Kobayashi et al, 1998;Niwa et al, 2005;Park et al, 2003;von Moltke et al, 1998;Wang et al, 2002;Xu and Desta, 2013). Therefore, the IC50 values were only determined for TDNPS that showed inhibition of more than 50%.…”
Section: Prescreening and Determination Of Ic50 Valuesmentioning
confidence: 99%
“…8.2 (Ki) (Ewald and Maurer, 2008) Paroxetine 0.01-0.05 (Schulz et al, 2012) 0.03-0.15 2.85 (Bertelsen et al, 2003) Clarithromycin 2.5-4 (Schulz et al, 2012) 3.3-5.4 116 (Burt et al, 2010) Saquinavir 0.1-5 (Schulz et al, 2012) 0.15-0.4 11.5 (von Moltke et al, 1998) in vitro Probe inhibitors (Dinger et al,…”
Section: Known Inhibitorsmentioning
confidence: 99%
“…All currently marketed PIs -atazanavir, amprenavir, fosamprenavir, indinavir, lopinavir, nelfinavir, ritonavir, and saquinavir -and the NNRTI delavirdine inhibit CYP3A4 (Piscitelli & Gallicano, 2001). According to Von Moltke et al (1998), ritonavir is the most potent CYP3A4 inhibitor and, consequently, has the most drug interactions, while amprenavir, indinavir, lopinavir, and nelfinavir appear to inhibit CYP3A4 equally, and saquinavir with the lowest inhibitory effect.…”
Section: Non-nucleoside Reverse Transcriptase and Protease Inhibitorsmentioning
confidence: 99%